PENGENALAN MEDIA TANAM ALTERNATIF HIDROGEL SEBAGAI PENAMBAH NILAI ESTETIKA DI YAYASAN “UNTUKMU SI KECIL” SUMBERSARI JEMBER - Hutami, Trapsila Siwi; Irsyadi, Muhammad Burhanuddin; Astuti, Sri Rejeki Dwi (PAPUMA: Journal of Community Services, 2024)
Increasing environmental awareness needs to be done to maintain good air quality. This can be done through reforestation. Plant cultivation can use planting media other than soil by using hydrogel as an alternative media which can add aesthetic value and economic value. A sense of environmental concern can be developed from an early age. The children at the "Untukmu Si Kecil" Foundation do not yet know about alternative hydrogel planting media. This service aims to introduce alternative hydrogel planting media to children as an addition to aesthetic value. This service was carried out in at “Untukmu Si Kecil” foundation, Sumbersari, Sumbersari, Jember with 16 participants. The methods used are lectures, direct practice and discussion. The service results showed that participants gained more in-depth knowledge about hydrogel planting media. Participants were very enthusiastic during the provision of materials and cultivation practices with hydrogel which could implement children's creativity in using colorful hydrogel. Apart from that, these results can beautify the room and table.